Erratum to: Mitochondrial and nuclear markers reveal a lack of genetic structure in the entocommensal nemertean Malacobdella arrokeana in the Patagonian gulfs - Fernandez Alfaya, Jose Elias (2014)
In the article, we noted some errors that we considered inaccurate and should be changed to prevent its spread.